Loyalitas Konsumen Plant-Based Meat Alternatives: Pengaruh Motivasi dan Subjective Well-Being: Customer Loyalty on Plant-Based Meat Alternatives: Effect of Motivation and Subjective Well-Being - Putra, Falih Ryan Dharmawan; Alversia, Yeshika (Jurnal Aplikasi Bisnis dan Manajemen, 2023)
In Indonesia, the number of vegetarians and vegetarian restaurants selling meat-free, plant-based alternatives, is growing. This is due to consumer encouragement and awareness of the benefits of eating healthier meals. There are, however, various more reasons why consumers should consume alternative meats. The aim of this study was to assess the influence of push and pull motivation on consumer loyalty by examining the subjective well-being of Indonesian vegetarian consumers who had ingested vegetable-based alternative meats. Quantitative research was conducted by delivering questionnaires online to 204 respondents. The study's findings indicate that both push and pull motivation have a positively significant influence on subjective well-being, with the push motivation component having a larger effect. Mood, that carries the highest loading factor value of 0.846, has the greatest influence on push motivation. Natural content, with a loading factor value of 0.808, is the dimension with the greatest influence on pull motivation. Loyalty is also significantly influenced by the two components of subjective well-being, perceived vitality, and affective well-being. The significance of this research is that it will serve as a reference for company management and marketers in developing a promotion strategy for plant-based meat products based on Indonesian vegetarian consumers. Keywords: loyalty, meat alternatives, motivation, plant-based, subjective well-being